(untitled) (New Jersey, 1990)
This book is divided into four parts: *) Part one discusses the nature of human language and the nature of grammar, linguistic creativity, language universals, and non-human communication. *) Part two examines the kinds of linguistic knowledge: sounds and sound patterns (phonetics and phonology); words and word formation (morphology); sentence structure (syntax); and meaning (semantics). *) Part three examines social aspects of language: Language variation , language change, and writing. *) The final section, Part four, on "The biological aspects of language", examines the neural basis of both spoken and sign language, the relations between brain, mind and language, the language processing by humans and computers
Ngôn ngữ học dẫn luận
Keywords: Language and languages,Linguistics